The impact of cyberloafing and physical exercise on performance: a quasi-experimental study on the consonant and dissonant effects of breaks at work - Santos, A. S.; Ferreira, A. I.; Ferreira, P. C. (Cognition, Technology and Work, 2020)
This study aims to examine the consonant and dissonant effects that cyberloafing and physical exercise may have on individuals’ performance as activities of occupying rest breaks at work. Built upon an innovative perspective, a laboratory quasi-experimental study was developed where a total of 124 participants performed two different tasks—a cognitive task measuring errors and omissions and a motor task. Their performance was evaluated after a cyberloafing or physical exercise break. Aligned with the cognitive dissonance theory, results revealed that physical exercise breaks had a positive effect on motor performance. Conscientiousness and engagement also presented a medium effect size, suggesting a trend to moderate the impact of cyberloafing breaks on cognitive performance. Theoretical and practical implications, as well as limitations of the study and areas for future research, were also explored.